The impact of improving environmental performance and implementing environmental cost allocation on company profitability - Pradhani, Tri Buana Wira; Shabana, Muhammad Ainul; Pandin, Maria Yovita R. (Jurnal Ekonomi, 2024)
Companies generally experience a business cycle, starting from the pioneering, growth, mature and decline stages. The company always maximizes performance and maintains company performance so that it can continue to compete with competitors and achieve optimal profits. In maintaining a company's financial performance, many factors must be considered, one of which is environmental factors. This research aims to discuss further the impact of improving environmental performance and implementing environmental cost allocation on company profitability, using the meta-analysis method. The data source used is secondary data, namely data obtained from previous research. The results show that almost all improvements in environmental performance and the use of environmental cost have an impact on company profitability.